Pentaerythritol tetradodecanoate (petd) production : a study on the effects of temerature and operating time of reaction - Mohd Ikhwan, Yusof (2006)
Pentaerythritol Tetradodecanoate (PETD) is a varnish additive that used in the magnetic wire coating. The esterification process is the main reaction in producing PETD. The raw materials to produce PETD are Pentaerythritol and Lauric Acid. The purification process of the raw materials is important before running the experiment to make sure the raw materials free from anything that debases, pollutes or contaminates. Sulfuric acid was used as a catalyst in the esterification between Pentaerythritol and Lauric acid. In this research, the thermodynamics study was carried based on the effect of operating and catalyst to the reaction. The dependent variables in the esterification to produce PETD are temperature and duration time of reaction. Otherwise, the independent variables are the amount of catalyst and reactants. This esterification was carried out at temperature between 180oC to 270oC and the duration time period of reaction between 8 hours to 24 hours. The reaction was conducted in the closed system batch reactor and the process was controlled in isothermal condition. The PETD that produced then was separated from water by using water distillation column. Then, the product was crystallized at the ambient temperature and the powder of PETD was obtained by crushing the crystal. The yield and color of the product were also observed. The product then was also analyzed using Thermogravimetric Analyzers (TGA). From the observation and analysis results, the optimum temperature and duration time of reaction was obtained at 220oC for 16 hours. Then, the result from the analysis was compared with the standard, Senox 410.